Affective Bond, Loneliness and Socioeconomic Aspects of an Elderly Population in Midwest, Brazil - Carlos Kusano Bucalen Ferrari; Graziele Souza Lira Ferrari; Lohany Dourado Nery; Daniela Franco dos Santos; Noeli Silva Pereira; Jéssica Silva Gonçalves; Geane Francis Santana (Archives of Nursing Practice and Care - Peertechz Publications, 2016)
Background: loneliness, a common feature among elderly people, can affect health and quality of life.  Objective: this article examined affective bond and marital status among elders in "Barra do Garças", municipality, Mato Grosso State, Midwest Brazil. Methodology: from the 3,593 elderly people, 300 engaged in the study which had been approved by the ethical committee on research. Results: there were more illiterate men than women (37.7% and 21.6%, respectively). In respect of income source there was a relative contingent of women with no income comparing to the men. Considering the socioeconomic class the majority of elderly, 68% belong to the less fortunate socioeconomic classes (D and E). Conclusion: it has been observed a higher contingent of elderly people with no affective bond or living alone which influence the quality of life of those elderly by increasing the psychosocial as well as the health-related risks, which was widely discussed according to the world's scientific literature.